1989
DOI: 10.14198/mdtrra1989.11.05
|View full text |Cite
|
Sign up to set email alerts
|

Nuevas citas y comentarios faunísticos sobre los quirópteros de la Comunidad Valenciana

Abstract: NUEVAS CITAS Y COMENTARIOS FAUNÍSTICOS SOBRE LOS QUIRÓPTEROS DE RESUMENSe aportan 92 citas quiropterológicas nuevas a las 110 menciones bibliográficas existentes hasta la actualidad, ampliándose así a 202 el total de referencias concretas conocidas en la Comunidad Valenciana. Igualmente, se cita por primera vez a Rhinolophus mehelyi, Myotis daubentoni y Myotis emarginatus, incrementándose el listado de especies de murciélagos valencianos a 19. Cabe añadir que 39 de las localidades citadas son nuevas. Se ha cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…References : Gisbert and Melendro (1978), ), Ibanez (1988, Meijide (1979), Otero et al (1978), Palmeirim (1990), Paz and Lope (1985), Samarra and Carol (1986), Sanchez-Canals and Guitiän (1988), Faus (1989), andSerra-Cobo et al (1986 This was one of the latest bat species to be reported in Spain (Balcells 1964). The known locations and those cited here indicate that it is a species widely distributed in all of Iberia ( Fig.…”
Section: Myotis Emarginatus (Geoffroy 1806)mentioning
confidence: 99%
“…References : Gisbert and Melendro (1978), ), Ibanez (1988, Meijide (1979), Otero et al (1978), Palmeirim (1990), Paz and Lope (1985), Samarra and Carol (1986), Sanchez-Canals and Guitiän (1988), Faus (1989), andSerra-Cobo et al (1986 This was one of the latest bat species to be reported in Spain (Balcells 1964). The known locations and those cited here indicate that it is a species widely distributed in all of Iberia ( Fig.…”
Section: Myotis Emarginatus (Geoffroy 1806)mentioning
confidence: 99%